Ethical leadership, emotional leadership, and quitting intentions in public organizations: Does employee motivation play a role?. Issue 2 (18th February 2020) - Ouakouak, Mohammed Laid; Zaitouni, Michel Georges; Arya, Bindu
Abstract : Purpose: Motivation constitutes a central topic for business management, because of its critical impact on job performance. Therefore, understanding whether and how the style of leadership adopted by leaders in organizations promotes and maintains employee motivation is of great interest to both scholars and practitioners. Drawing on self-determination theory, this study investigates how ethical and emotional styles of leadership influence employee motivation and thus job performance. Design/methodology/approach: An empirical study was conducted in the public sector in Kuwait. About 607 employees participated in this study. Structural equation modeling techniques were used for testing the causal relationships between constructs. Findings: Results of our study indicate that both ethical and emotional leaderships enhance employee motivation. Furthermore, employee motivation has a positive impact on job performance. The results also show that job performance exerts a negative effect on quitting intentions. Finally, interest in the private sector moderates the job performance–quitting intentions relationship. Practical implications: These findings provide theoretical contributions to the extant literature, as well as important practical implications for managers. Originality/value: This study demonstrates the role of both ethical and emotional leaderships in shaping employee behaviors. To the best of our knowledge, this research is among the few that provides initial evidence regarding quitting intentions as an outcome of the impact of ethical and emotional leaderships on employee motivation and individual performance in Kuwait.